Comparison analysis of MANET routing protocols to identify their suitability in smart environment - Devi, Munisha; Singh Gill, Nasib (International Journal of Engineering and Technology, 2018)
Mobile Ad Hoc Network (MANET) is a temporary structure; it is self-adjustable, random network without any topology. MANET is guiding in varied area of smart environment and applications to deal with the issues faced by individuals in daily life. Routing is a very interesting research area in mobile networks. Many researchers have come up with their opinion but it is very difficult to say which protocol performs best in different network scenarios such as more overload, increasing load density, etc. This paper highlights different categories of protocols and also provides a performance comparison of these protocols, and tries to suggest which protocol may perform best in a large network. Several routing protocols are compared with respect to Routing Approaches, Routing Table, Route Selection, Route Discovery, Route Maintenance, Protocol Type, Operation, Advantages, Disadvantages, etc. By looking at performance characteristics and metrics of all categories of routing protocols, a number of conclusions can be drawn for each category that may help the researchers.Â
Keywords: ADHOC; AODV; DSR; DSDV; MANET; TORA.